(CAG)n loci as genetic modifiers of age at onset in patients with spinocerebellar ataxia type 1 from mainland China. (15th April 2019) - Wang, P.; Chen, Z.; Peng, Y.; Cao, L.; Li, X.; Wang, C.; Yang, H.; Peng, H.; Shi, Y.; Zhou, X.; Li, T.; Feng, L.; et al.
Abstract : Background and purpose: The expanded repeat length in ATXN1 negatively correlates with age at onset (AAO) of spinocerebellar ataxia type 1 (SCA1) but can explain only part of it, indicating that other factors affect AAO. Some studies have explored the influence of non‐causative CAG repeats on the AAO of SCA patients. However, studies on Chinese SCA1 patients regarding candidate modifier factors involved in the variability in AAO are rare. Methods: In all, 152 Chinese SCA1 patients who were genotyped for ATXN1 and nine other (CAG) n ‐containing genes were enrolled. Regression analysis was performed to determine the effect of the expanded allele of ATXN1 (linear and quadratic effects) on AAO. Then, different models were used to explore the modulatory effect of nine other (CAG) n ‐containing genes. Results: Our results verified the negative effect of the expanded allele in ATXN1 by regression analysis. Some (CAG) n ‐containing genes including TBP, ATN1 and HTT modified AAO with variance ranging from 0.8% to 3.8% and tended to decrease or delay AAO. However, no modifier effects of ATXN2, ATXN3, CACNA1A, ATXN7, KCNN3, RAI1 and normal ATXN1 alleles in trans were detected. Conclusion: By using interaction analyses, TBP, ATN1 and HTT were determined to have modifying effects. Our study revealed that differences in modulation may be due to ethnic and geographic diversity across different populations. Furthermore, the variability of AAO was not completely explained by the genetic modifiers examined here, suggesting that other genetic or environmental factors are involved in these diseases.